Cataract Origin, Diagnosis and Modern Clinical Diagnostic Methods - Abbos, Shodmanov; Urol o’g’li, Sattorov Bobur; Mirzohid o’g’li, Saydullayev Dilshod (American Journal of Bioscience and Clinical Integrity, 2025)
General Background: The most common cause of vision loss on a global scale, affecting individuals mostly over the age of 40, is cataracts. This condition leads to clouding of the eye’s lens, resulting in gradual vision deterioration and eventual blindness if left untreated. While aging is the primary contributing factor, genetic predisposition, metabolic disorders, and external influences such as prolonged UV exposure and smoking can accelerate its onset. Specific Background: Cataracts can be classified based on their cause and presentation, including age-related (senile), traumatic, congenital, and drug-induced types. The International Classification of Diseases (ICD-10) provides a systematic framework for diagnosing and managing the condition. Despite its widespread prevalence, early symptoms of cataracts often go unnoticed, leading to delays in diagnosis and treatment. Knowledge Gap: While extensive research has been conducted on the biochemical mechanisms and risk factors contributing to cataract formation, gaps remain in understanding its precise pathogenesis. The role of environmental and lifestyle factors in accelerating lens opacity is not yet fully understood. Additionally, while surgical interventions are highly effective, non-surgical treatments have shown limited success. Aims: This study aims to explore the causes, diagnostic methods, and progression of cataracts while highlighting the latest advancements in clinical diagnosis and treatment. Results: Our findings underscore the importance of early detection through modern ophthalmologic techniques such as slit-lamp examination and ophthalmoscopy. Ultrasonic phacoemulsification, a minimally invasive surgical procedure, remains the preferred treatment, boasting a success rate of over 99%. Novelty: This research provides a structured classification of cataracts and highlights emerging diagnostic techniques that have the potential to enhance early detection and treatment effectiveness. Implications: The study emphasizes the necessity of regular eye examinations for individuals at higher risk, along with preventive measures such as UV protection and effective management of metabolic disorders to reduce cataract incidence. Future research should focus on developing pharmacological treatments to slow disease progression and improve surgical outcomes.